The Implementation of Integrated Curriculum Management in Improving Student Academic Achievement at Integrated Junior High Schools - Risalatun Nisa Nirkhayadi; Neneng Nurmalasari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
Educational institutions are a place to produce quality young generations. Because education is very influential in life, both nationally and religiously. Quality educational institutions will produce quality learning as well. However, its success is influenced by the curriculum management implemented in the institution. Therefore, curriculum management is needed in developing the quality of education in educational institutions. The purpose of this study was to find out the planning, implementation and influence of the integrated curriculum at SMP Terpadu Dampasan Miftahul Anwar. This study uses a qualitative approach through the observation process at SMP Terpadu Dampasan Miftahul Anwar. The data obtained were based on interviews and documentation. The results of this study indicate that the integrated curriculum management at SMP Terpadu Dampasan Miftahul Anwar is running well, indicated by the efforts made by all parties involved, starting from the leadership of the Mifthaul Anwar Islamic boarding school, the principal of SMP Terpadu Dampasan Miftahul Anwar